Electromagnetic interference on artificial heart pacemaker - Sahrani, S.; Semangin, N.; Suhaili, S.; Awg Mat, D.A.; Osman, M.S; Sawawi, M. (IEEE, 2009)
Electromagnetic interference (EMI) due to Radio Frequency (RF) is known to cause interference in electronics devices. Interference may cause devices such as pacemaker to malfunctions with potentially adverse consequences. Exposure of electromagnetic interference comes from digital cellular telephones that are commonly used nowadays. This paper describes the preliminary case study on the effect of the EMI interference with a pacemaker. Temperatures were calculated at various frequencies to investigate the effect. Higher temperatures may cause discomfort to the patient.